Socioeconomic disparities: a more important risk factor for advanced-stage oral cancer in Florida than smoking? - Garrett Forman; Uche C. Ezeh; Isabella Buitron; Sophia Peifer; Liana Shtern; Tonya Aaron; Abdurrahman Al-Awady; Isildinha M. Reis; Erin R. Kaye; Elizabeth Nicolli; David Arnold; Francisco Civantos; et al. (Cancer Causes & Control, 2025)
Purpose To explore the associations between sociodemographic factors with advanced-stage oral cavity cancer (OCC) presentation among Floridians. Methods Demographic and cancer data on OCC patients ( n = 7,826) diagnosed between 2010 and 2017 were retrieved from the Florida Cancer Data System (FCDS). Census tract median income and percentage of population with a bachelor’s degree or higher were used to infer income and education. Pearson’s chi-square tests of independence were used to compare sociodemographic factors between racial/ethnic groups and staging groups. Multinomial logistic regression analyzed predictors of advanced disease. Incidence and percent late-stage diagnosis versus income were mapped using ArcGIS Pro. Results Among 5,252 cases analyzed: 5.7% were Black, 82.4% White Non-Hispanic, 61.5% male, 63.3% publicly insured, 6.5% uninsured, 58.7% current or former smokers, and 73.0% urban residents. Black patients were more likely to present with advanced disease, be single/unmarried, uninsured, and less likely to be former smokers. Male sex, Black race, non-married status, no insurance, Medicaid, VA/military insurance, and lower educational status were associated with increased risk of regional vs. early disease in multivariable analysis (MVA) ( p < 0.05). These factors, in addition to Medicare, were associated with distant disease in MVA. Geospatial mapping revealed higher rates of regional and distant disease presentation in the Tampa Bay and Orlando areas. Conclusion Black race, male sex, non-married status, lower education, Medicaid, VA/Military insurance and no insurance were associated with advanced OCC in Florida. Smoking status was not associated with advanced disease presentation after adjusting for sociodemographic variables.

Peak oxygen uptake in older adults with heart failure: a systematic review and meta-analysis - Veronika Schmid; Sarah Paterson; Christopher Weinkauf; Jing Wang; Corey R. Tomczak; David Niederseer; Jan Vontobel; Daniel E. Forman; Martin Halle; Michael D. Nelson; Stephen J. Foulkes; Mark J. Haykowsky (GeroScience, 2025)

Lower muscle mitochondrial energetics is associated with greater phenotypic frailty in older women and men: the Study of Muscle, Mobility and Aging - Theresa Mau; Haley N. Barnes; Terri L. Blackwell; Philip A. Kramer; Scott R. Bauer; David J. Marcinek; Sofhia V. Ramos; Daniel E. Forman; Frederico G. S. Toledo; Russell T. Hepple; Stephen B. Kritchevsky; Steven R. Cummings; et al. (GeroScience, 2023)

Development of an Injury Risk Function for the Anterior Pelvis Under Frontal Lap Belt Loading Conditions - David Moreau; Pavel Chernyavskiy; Sara Sochor; Bronislaw Gepner; Jason Forman; Martin Östling; Jason R. Kerrigan (Annals of Biomedical Engineering, 2023)

Demonstrating Contribution of Components of Fixed-Dose Drug Combinations Through Longitudinal Exposure-Response Analysis - Asbjørn Nøhr-Nielsen; Theis Lange; Julie Lyng Forman; Theodoros Papathanasiou; David J. R. Foster; Richard N. Upton; Ole Jannik Bjerrum; Trine Meldgaard Lund (The AAPS Journal, 2020)

The Oxygen Paradox, the French Paradox, and age-related diseases - Joanna M. S. Davies; Josiane Cillard; Bertrand Friguet; Enrique Cadenas; Jean Cadet; Rachael Cayce; Andrew Fishmann; David Liao; Anne-Laure Bulteau; Frédéric Derbré; Amélie Rébillard; Steven Burstein; et al. (GeroScience, 2017)

Canine genome assembly correction facilitates identification of a MAP9 deletion as a potential age of onset modifier for RPGRIP1-associated canine retinal degeneration - Oliver P. Forman; Rebekkah J. Hitti; Mike Boursnell; Keiko Miyadera; David Sargan; Cathryn Mellersh (Mammalian Genome, 2016)

Dietary habits and gastric cancer risk in north-west Iran - Mohammadreza Pakseresht; David Forman; Reza Malekzadeh; Abbas Yazdanbod; Robert M. West; Darren C. Greenwood; Jean E. Crabtree; Janet E. Cade (Cancer Causes & Control, 2011)

Identification and characterisation of ssrA in members of the Helicobacter genus - Quanjiang Dong; Li Zhang; Khean-lee Goh; David Forman; Jani O’Rourke; Andrew Harris; Hazel Mitchell (Antonie van Leeuwenhoek, 2007)

Maternal Risk Factors for Testicular Cancer: A Population-Based Case–Control Study (UK) - Carol A.C. Coupland; David Forman; Clair E.D. Chilvers; Gwyneth Davey; Malcolm C. Pike; R. Tim D. Oliver (Cancer Causes & Control, 2004)

Monitoring the changing pattern of esophago-gastric cancer: data from a UK regional cancer registry - John Wayman; David Forman; S. Michael Griffin (Cancer Causes & Control, 2001)

Nitrate in drinking water and the incidence of gastric, esophageal, and brain cancer in Yorkshire, England - Jennifer H. Barrett; Roger C. Parslow; Patricia A. McKinney; Graham R. Law; David Forman (Cancer Causes & Control, 1998)